Inheritance mechanism of yield and yield components in tomato (Bangladesh Journal of Agricultural Research, 2016)
A set of 9x9 half diallel cross comprising of promising genotypes was studied to analyze the inheritance pattern of yield components in tomato. Haymans analysis of variance (ANOVA) indicated importance of both additive and nonadditive genetic components for all the thirteen yield contributing characters. The ANOVA showed unidirectional dominance, asymmetrical gene distribution and residual dominance effects for all the characters studied. Five out of the thirteen characters viz., number of flowers/cluster, individual fruit weight, fruit breadth, number of locules and number of seeds/fruit followed the simple additive-dominance genetic model. The rest of the characters showed non-allelic gene interaction or epistasis. P6 had most of the dominant genes for both number of flowers/cluster and number of locules, while P3 contained most dominant genes for individual fruit weight and P5 possessed that for both fruit breadth and number of seeds/fruit. The estimates of components of variance demonstrated involvement of both additive and dominant components in the inheritance of all those five characters. The distribution of dominant and recessive genes was equal in the parents for only fruit breadth. There was drastic influence of environment on these characters following simple additive-dominance genetic model except fruit breadth.Bangladesh J. Agril. Res. 41(2): 335-344, June 2016